Clinical and Physiological Significance of F-Wave in Spinocerebellar Ataxia Type 3 - Cai, Qiong; Xu, Wenxiao; Liao, Songjie; Liang, Yinxing; Wu, Chao; Li, Xunhua (Frontiers in Neurology, 2020)
Objective To evaluate the characteristics of F-wave in spinocerebellar ataxia type 3 (SCA3) patients and preclinical carriers of SCA3 gene mutation (PreSCA3), and explore the relationship between disease severity and F-wave parameters and evaluate F-wave parameters as potential biomarkers for monitoring of disease progression in SCA3. Methods We performed F-wave recordings in median, ulnar and tibial nerves of 39 SCA3 patients, 20 PreSCA3 and 27 healthy controls, and compared F-wave parameters between them. Results In all nerves studied, the mean F-wave amplitude, maximum F-wave amplitude and F/M amplitude ratio were significantly increased in the SCA3 patients in comparison with the normal controls. And the minimal F-wave latency of SCA3 patients was significantly prolonged and the F-wave persistence (%) was significantly decreased in the median nerve. For the PreSCA3, the maximum F-wave amplitude was significantly higher than normal controls for both median, ulnar and tibial nerves. The mean F-wave amplitude and F/M amplitude ratio in all nerves were comparable between PreSCA3 and normal controls. The frequency of giant F-wave and frequency of patients with giant F-wave were similar between PreSCA3 and SCA3. The values of F/M amplitude ratio in both median, ulnar and tibial nerves were correlated positively with disease severity and disease duration. Conclusion Significant F-wave abnormalities occur in patients with SCA3, even in PreSCA3. F-wave may therefore reveal subclinical alterations and provide objective parameters for evaluating the progression of SCA3.